Exploring Consciousness And The Subconscious Mind: A Comparative Study Of The Panchkosha Theory And Freud’s Unconscious - Ms. Jyoti Arora; Dr. Jay Singh; Dr. Ravinder Kaur (Revista Electronica de Veterinaria, 2024)
In Eastern philosophy, especially within the Vedantic paradigm, the Panchkosha hypothesis provides a comprehensive and stratified interpretation of human consciousness, transitioning from the concrete physical body to the most refined levels of pure awareness. This conception originates from ancient Indian scriptures such as the Taittiriya Upanishad and depicts the self as a multifaceted entity, encompassing physical, mental, emotional, and spiritual qualities